Antibiotic Protocols for Endophthalmitis Prophylaxis Following Open-Globe Repair: A Survey of U.S. Residency Programs - Fell, David; Blomquist, Preston H. (Journal of Academic Ophthalmology, 2023)
Purpose To assess the various approaches to endophthalmitis prevention following traumatic open-globe injury (OGI) repair.Methods A research electronic data capture (REDCap) questionnaire evaluating the usage of antibiotics and steroids in patients with OGI was distributed to program directors of all U.S. ophthalmology residency programs using the Association of University Professors of Ophthalmology program directors' listserv. Completed questionnaires were analyzed for treatment patterns.Results The REDCap questionnaire was distributed to 111 programs, with 32 residency programs responding. Two responses were excluded. Ninety percent (27/30) of included programs used perioperative intravenous (IV) antibiotics, with 78% (21/27) of those giving one dose only. At the time of surgery, 27% (8/30) of programs gave intravitreal antibiotics and 60% (18/30) gave subconjunctival antibiotics. Postoperatively, 100% (30/30) gave topical antibiotics and 97% (29/30) gave topical steroids. Only 53% of responders discharged patients on oral antibiotics. Of the three programs who did not use IV antibiotics, all three gave intravitreal therapy and one also discharged patients on oral antibiotics.Conclusion There is a large variation in practice patterns for endophthalmitis prophylaxis among residency programs. Further investigation is needed to compare rates of endophthalmitis between these protocols and establish a safe and minimally burdensome standard of care.
Keywords: endophthalmitis; antibiotic prophylaxis; open-globe injury